Adapting a Virtual World for Theatrical Performance. - Geigel, Joe; Schweppe, Marla; Huynh, David; Johnstone, Brian (Computer (00189162), 2011)
Virtual reality technology now makes it possible to completely realize theatrical performances in a virtual space, but existing virtual world interfaces are too cumbersome for this purpose. Researchers are working to develop virtual theatre systems with more natural and intuitive interfaces.